1997
DOI: 10.1111/j.1399-0039.1997.tb02854.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome subunits, low‐molecular‐mass polypeptides 2 and 7 are hyperexpressed by target cells in autoimmune thyroid disease but not in insulin‐dependent diabetes mellitus: implications for autoimmunity

Abstract: Autoimmune thyroid diseases (AITD) and insulin-dependent diabetes mellitus (IDDM) are two autoimmune syndromes of unknown etiology with common immune features. One is that the target cells, thyrocytes and pancreatic islet beta cells respectively, hyperexpress several proteins encoded in the HLA region: HLA class I, HLA class II and transporter associated with antigen processing (TAP-1): the clinical course and many aspects of the immunopathology are, however, quite different. Low-molecular-mass polypeptides 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…One of the early pathogenic lesions of autoimmune diabetes in both humans and rodent models is hyperexpression of correctly assembled MHC class I molecules on the surface of ␤ cells, a step requiring intact proteasome function (23,33,42,57,73,85,89). Early up-regulation of LMP2 or the TAP1 protein, a transporter protein delivering proteasome-cleaved fragments to MHC class I molecules, is similarly observed in target tissues affected by autoimmune thyroid disease or diabetes (86). Furthermore, immortalized NOD mouse islet cell lines overexpress NF-B (73), the processing of which we have now shown to be dependent on LMP2 and which is required for resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 74%
“…One of the early pathogenic lesions of autoimmune diabetes in both humans and rodent models is hyperexpression of correctly assembled MHC class I molecules on the surface of ␤ cells, a step requiring intact proteasome function (23,33,42,57,73,85,89). Early up-regulation of LMP2 or the TAP1 protein, a transporter protein delivering proteasome-cleaved fragments to MHC class I molecules, is similarly observed in target tissues affected by autoimmune thyroid disease or diabetes (86). Furthermore, immortalized NOD mouse islet cell lines overexpress NF-B (73), the processing of which we have now shown to be dependent on LMP2 and which is required for resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 74%
“…It is likely that the tissue levels of LMP2 change throughout the course of the autoimmune process in a tissue-specific manner. For example, Vives-Pi and colleagues, studying eight patients with Graves disease patients and four with type 1 diabetes, reported that thyroid glands expressed high but variable levels of LMP2 and LMP7, whereas pancreases had levels similar to those found in healthy controls [21]. LMP2 increase did not always correspond to a similar LMP7 increase, in keeping with the notion that these two subunits are not always assembled together [22] in the immunoproteasome, contrary to the pairing of LMP2 and LMP10 [23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the immune response in GD declines after thyroidectomy [5], and GD thyroid tissue engrafted into immunodeficient mice produces anti-thyroid antibodies [6]. The thyroid tissue itself undergoes many changes in GD, such as thyroid follicular cells (TFCs) express HLA class I and class II [7,8], TAPs and LMPs [9], HLA-DMA [10], ICAM-1 and NCAM [11e14], CD40 [15], Fas and Fas-L molecules [16] and also produce CXCL12 [17] and IL-16 [18]. In addition, GD entails the frequent extensive infiltration of the thyroid gland by lymphocytes, macrophages and dendritic cells making up germinal centers containing Thyroid Peroxidase (TPO) and Thyroglobulin (TG) specific B-lymphocytes [19].…”
Section: Introductionmentioning
confidence: 99%